Effect Of Cooperative Learning Strategies On Social Competence And Academic Achievement In Science Among 9th Grade Students (Journal of Namibian Studies : History Politics Culture, 2023)
This study investigates the impact of cooperative learning strategies, specifically the Student Team Achievement Divisions (STAD) method, on the social competence and academic achievement in science among 9th-grade students at Khalsa College Public School, Amritsar. The study compares the outcomes of cooperative learning strategies with conventional teaching methods. The research employs a sample size of 40 students, and the tools utilized for assessment include the Social Competence Scale developed by Dr. Sharma, Dr. Mrs. Shukla, and Shukla (2015) to measure social competence and a self-made achievement test in science for assessing academic achievement. The study takes place at Khalsa College Public School in Amritsar, providing insights into the effectiveness of cooperative learning strategies within this specific educational setting. The findings from this research contribute to the broader understanding of the influence of teaching methods on both social competence and academic achievement in science among 9th-grade students. The results of this study will providing valuable insights for educators, administrators, and policymakers. Understanding the impact of cooperative learning strategies on social competence and academic achievement can inform instructional practices, leading to improved learning outcomes for students in the 9th grade.